Atopic eczema: burden of disease and individual suffering – results from a large EU study in adults. (6th June 2019) - Ring, J.; Zink, A.; Arents, B.W.M.; Seitz, I.A.; Mensing, U.; Schielein, M.C.; Wettemann, N.; de Carlo, G.; Fink‐Wagner, A.
Abstract: Background: Atopic eczema (AE, atopic dermatitis) is one of the most common non‐communicable inflammatory skin diseases affecting 1–5% of the adult population in Europe with marked impairment in quality of life. In spite of great progress in understanding the pathophysiology of disturbed skin barrier and immune deviation, AE still represents a problem in daily clinical practice. Furthermore, the true impact of AE on individual suffering is often not recognized. Objectives: With a large European study, we wanted to provide insights into the actual suffering and individual burden of disease in adult patients with AE. Methods: A total of 1189 adult patients (18–87 years, 56% female) with moderate to severe AE were recruited in nine European countries by dermatologists or allergists together with the help of patient organizations. A computer‐assisted telephone interview was performed by experienced interviewers between October 2017 and March 2018. The following instruments were used to assess severity or measure quality of life: Patient‐Oriented Eczema Measure (POEM), Dermatology Life Quality Index (DLQI), Hospital Anxiety and Depression Scale (HADS‐D) and a newly developed Atopic Eczema Score of Emotional Consequences (AESEC). Patients were also asked to self‐assess the severity of their disease. Results: Despite current treatment, 45% of participants still had actual moderate to very severe AE in POEM. Due to their skin disease, 57% missed at least 1 day of work in the preceding year. DLQI showed moderate to extremely large impairment in 55%. According to HADS‐D, 10% scored on or above the threshold of eight points with signs of depressive symptoms. Assessed with AESEC, 57% were emotionally burdened with feelings such as 'trying to hide the eczema', 'feeling guilty about eczema', having 'problems with intimacy' and more. Of persons actually suffering from severe AE, 88% stated that their AE at least partly compromised their ability to face life. Conclusions: This real‐life study shows that adults with a moderate to severe form of AE are suffering more than what would be deemed acceptable. There is a need for increased awareness of this problem among healthcare professionals, policymakers and the general public to support research in the development of new and more effective treatments and provide access to better and affordable health care for affected patients.